2014
DOI: 10.1371/journal.pone.0092518
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of Singlet Oxygen and Hydrogen Peroxide on Bacterial Community Composition in a Humic Lake

Abstract: Light excitation of humic matter generates reactive oxygen species (ROS) in surface waters of aquatic ecosystems. Abundant ROS generated in humic matter rich lakes include singlet oxygen (1O2) and hydrogen peroxide (H2O2). Because these ROS differ in half-life time and toxicity, we compared their effects on microbial activity (14C-Leucine incorporation) and bacterial community composition (BCC) in surface waters of humic Lake Grosse Fuchskuhle (North-eastern Germany). For this purpose, experiments with water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Previous experiments performed in Lake Grosse Fuchskuhle revealed that PnecC is sensitive to hydrogen peroxide and depends on the presence of H 2 O 2 detoxifiers, meaning organisms that encode catalase peroxidase (Glaeser et al . ). This observation parallels those in the marine environment, where highly abundant organisms such as Prochlorococcus lack the same function, leaving the organisms to rely on the ‘leaky’ function of other marine organisms to remove peroxides from the environment (Morris et al .…”
Section: Resultsmentioning
confidence: 97%
“…Previous experiments performed in Lake Grosse Fuchskuhle revealed that PnecC is sensitive to hydrogen peroxide and depends on the presence of H 2 O 2 detoxifiers, meaning organisms that encode catalase peroxidase (Glaeser et al . ). This observation parallels those in the marine environment, where highly abundant organisms such as Prochlorococcus lack the same function, leaving the organisms to rely on the ‘leaky’ function of other marine organisms to remove peroxides from the environment (Morris et al .…”
Section: Resultsmentioning
confidence: 97%
“…For example, Febria et al (2006) found that the production of hydrogen peroxide (H 2 O 2 ) in two delta lakes that were also sampled herein (CON and TK) outpaced the rate of removal during a period of uninterrupted sunshine in 2004, leading to an accumulation of H 2 O 2 within the water columns. Production of ROS during previous studies of DOM photodegradation has been observed to inhibit community-level rates of carbon production (Scully et al 2003;Anesio et al 2005;Glaeser et al 2014) and result in changes in bacterial community composition (Glaeser et al 2010(Glaeser et al , 2014. Further, in a prior study by Lund and Hongve (1994), declines in BA of up to 60% were observed after only an hour when UV-irradiated DOM was mixed with bacteria.…”
Section: Photoreactivity Of Mackenzie River Freshet Dommentioning
confidence: 94%
“…To some extent, therefore, irradiation of DOM by sunlight simultaneously stimulates and inhibits heterotrophic bacterial production (BP) (Scully et al 2003;Ruiz-Gonzalez et al 2013), leading to complex interactions that can result in enhanced, negative, mixed, or no effect on bacterial community metabolism (Lonborg et al 2016). In addition, the bacterial community composition may be altered either by exposure to ROS (Glaeser et al 2010;Glaeser et al 2014) or in response to the increased lability of the pool of DOM substrate (Judd et al 2007;Piccini et al 2009;Paul et al 2012;Ward et al 2017), giving rise to a species assemblage that is better suited to the ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment has been seen in genes related to sterol metabolism and transport activity through multidrug resistance and pleiotropic drug resistance types of ABC transporters (Wakao et al ., ). 1 O 2 exists in aquatic and terrestrial environments, where it is generated by photosensitizing humic substances (Frimmel et al ., ; Steinberg et al ., ) and is known to affect microbial populations including phytoplankton (Glaeser et al ., , ). Activation of sterol metabolism, a lipid component of the plasma membrane, and transporters may reflect how a soil‐dwelling microalga such as C. reinhardtii has pathways to respond to 1 O 2 that is generated not only in the chloroplast, but also in other compartments.…”
Section: Singlet Oxygen Signalingmentioning
confidence: 99%